Sensitivity of AMPA receptor channel to calcium oscillations: A computational study - Antunes, Gabriela [UNESP]; Simões-de-Souza, Fábio M.; Roque, Antônio C. (Elsevier, 2003)
We used a computational model of biochemical pathways that are involved in the phosphorylation/dephosphorylation of AMPA receptor to study the receptor responses to calcium oscillations. In the model, the biochemical pathways are assumed to be located immediately under the postsynaptic membrane and we included three states of AMPA receptor: dephosphorylated, and phosphorylated in one or in two sites. To characterize the effects of calcium oscillations on the AMPA receptor, we exposed the model to stimuli with three varying parameters, namely frequency, number of pulses and calcium spike duration. Our model showed sensitivity to all of these three parameters. © 2002 Elsevier Science B.V. All rights reserved.
Keywords: AMPA receptor; Biochemical networks; Calcium oscillations; Plasticity; Calcium; Cell membranes; Sensitivity analysis; Phosphorylation; Biochemistry; calcium; biochemistry; calcium signaling; chemical parameters; computer program; computer simulation; controlled study; dephosphorylation; frequency modulation; mathematical model; postsynaptic membrane; priority journal; protein phosphorylation; sensitivity analysis; spike wave